Heat Shock Protein 90 (Hsp90) Expression and Breast Cancer - Christos A. Papadimitriou; Konstantinos Koutsoukos; Evangelos Bournakis; Flora Zagouri (MDPI AG, 2012)
Hsp90 is an abundant protein in mammalian cells. It forms several discrete complexes, each containing distinct groups of co-chaperones that assist protein folding and refolding during stress, protein transport and degradation. It interacts with a variety of proteins that play key roles in breast neoplasia including estrogen receptors, tumor suppressor p53 protein, angiogenesis transcription factor HIF-1alpha, antiapoptotic kinase Akt, Raf-1 MAP kinase and a variety of receptor tyrosine kinases of the erbB family. Elevated Hsp90 expression has been documented in breast ductal carcinomas contributing to the proliferative activity of breast cancer cells; whilst a significantly decreased Hsp90 expression has been shown in infiltrative lobular carcinomas and lobular neoplasia. Hsp90 overexpression has been proposed as a component of a mechanism through which breast cancer cells become resistant to various stress stimuli. Therefore, pharmacological inhibition of HSPs can provide therapeutic opportunities in the field of cancer treatment. 17-allylamino,17-demethoxygeldanamycin is the first Hsp90 inhibitor that has clinically been investigated in phase II trial, yielding promising results in patients with HER2-overexpressing metastatic breast cancer, whilst other Hsp90 inhibitors (retaspimycin HCL, NVP-AUY922, NVP-BEP800, CNF2024/BIIB021, SNX-5422, STA-9090, etc.) are currently under evaluation.